Can We Separate Oral Lichen Planus from Allergic Contact Dermatitis and Should We Patch Test? A Systematic Review of Chronic Oral Lichenoid Lesions. Issue 3 (May 2021) - Rahat, Shahmina; Kashetsky, Nadia; Bagit, Ahmed; Sachdeva, Muskaan; Lytvyn, Yuliya; Mufti, Asfandyar; Maibach, Howard I.; Yeung, Jensen
Abstract : This systematic review summarizes characteristics and treatment outcomes of dental amalgam–associated oral lichenoid lesions (OLLs) and oral lichen planus (OLP). Embase and MEDLINE were searched for original studies on OLLs or OLP associated with dental amalgam. Data extraction was completed from 44 studies representing 1855 patients. Removal of amalgam restorations led to complete resolution in 54.2% (n = 423/781), partial resolution in 34.8% (n = 272/781), and no resolution in 11.0% (n = 86/781) of the patients with OLLs, whereas complete resolution occurred in 37.1% (n = 72/194), partial resolution in 26.3% (n = 51/194), and no resolution in 36.6% (n = 71/194) of the patients with OLP. For patients with OLLs, 91.6% of the patients with positive patch tests and 82.9% with negative patch tests had improvement with removal of amalgam, whereas for patients with OLP, 89.2% of the patients with positive patch tests and 78.9% with negative patch tests had improvement with removal of amalgam. Our results suggest improvement occurs, regardless of patch testing status. Abstract : Supplemental digital content is available in the text.